Reliability-based assessment of the effect of climatic conditions on the corrosion of RC structures subject to chloride ingress - El Hassan, Jinane; Bressolette, Philippe; Chateauneuf, Alaa; El Tawil, Khaled (Engineering structures, 2010)
The corrosion of reinforced concrete due to chloride ingress depends on many uncertain factors, such as material properties, environment and loading. This paper proposes a reliability model to deal with initiation and propagation of the RC corrosion process, in order to determine the probability distributions of the time to corrosion initiation and the time to failure of RC members subjected to chloride ingress. The present work emphasizes the impact of climatic conditions, namely temperature and relative humidity, on the two phases of corrosion. The application to RC bridge girders shows the importance of various climatic conditions on the structural reliability, through comprehension analysis of the effect of climatic parameters, as well as the choice of steel bar diameters.